An entrepreneur's manifesto - Mariotti, Steve, 1953- ([West Conshohocken, PA] : Templeton Press, 2015)
In an increasingly competitive world market, how does the United States rank? Many Americans are worried about the economic state of their nation, especially now that countries like China are becoming ever more economically powerful. What does America need to both stabilize and energize its economy?Entrepreneurship, Steve Mariotti claims, is key. An Entrepreneur's Manifesto is Mariotti's rallying cry for the world to recognize the potential that business creation holds, not only for the individual but for the economy as well. Mariotti explores the ways entrepreneurship affects schools and pris.
Entrepreneurship can be taught--to anyone -- Nurturing the entrepreneurial mind-set -- Who are the world's entrepreneurs? -- Should governments help promote entrepreneurship? -- A teaching revolution -- The digital revolution : technology levels the global playing field -- On the cusp : a financing revolution -- A prison revolution : desperately needed -- The social enterprise revolution : entrepreneurs solving social problems -- An entrepreneur's manifesto.
Includes index.
Keywords: New business enterprises; Entrepreneurship; Entrepreneurship -- Study and teaching; Entrepreneurship -- Social aspects